ONLINE PROMOTION TRAINING FOR WASTRA PELINGGIH BUSINESS IN PAKSEBALI VILLAGE, KLUNGKUNG DISTRICT - I Putu Widyarsana; Putu Eny Suhardiyani; I Wayan Gede Lamopia; I Gusti Putu Hardi Yudana (Jurnal Pengabdian Informatika, 2023)
Bali is famous for its religious culture which is carried out by its Hindu population. To support the ceremony, the community needs ceremonial equipment, namely Wastra. In Bali, wastra is also usually referred to as clothing, especially wastra in the use of Pelinggih which has its own meaning and symbol. This is what triggers the emergence of the Wastra business. The dedication partner is Mrs. Ni Wayan Sitiari who has been managing her textile business for about 5 years. Based on the results of the interviews, Partners sell their silk fabrics directly in the market without using technology. Activities for this PKM started with outreach activities followed by online promotion training and closed with activity evaluation. Socialization is carried out by discussing the plans and schedule of activities. In the online promotion training activities, material is given regarding the meaning, benefits and advantages of online promotion compared to conventional methods, strategies for increasing marketing with online promotions and how to start online promotions. The last activity, namely evaluation, is carried out to find out how much partners feel this activity is useful for increasing future promotions. Based on the results of interviews on mastery of the material, it was found that the participants had achieved 95% mastery of the material. The output produced in this service is an increase in competitiveness in the form of increased sales